VYTAUTAS KAVOLIS: PSYCHOBIOGRAPHY OF VINCAS KUDIRKA - Noreika, Alvydas (Sociologija. Mintis ir veiksmas, 2016)
The article deals with the biography of Vincas Kudirka, one of the leaders of Lithuanian National Revival in XIX century, written by Lithuanian-American scientist Vytautas Kavolis (1930–1996). It is stated that, instead of its overt focus on the person only, the biography, named Žmogaus genezė (The Origin of Man) (1963), actually deals with the whole social group, Lithuanian national movement, and its psychic life. It is argued that scrutinizing life-history of its leader Kavolis aims at disclosing the emotionality shared by the members of the movement. Therefore by its nature the biography is a work of social psychology. Such approach to Žmogaus genezė is based on two arguments. First, in his analysis Kavolis uses the psycho-historical method developed by American psychoanalyst Erik H. Erikson. The main presupposition of this method asserts that intellectual or political leader represents the collective psychic processes taking place in his followers. Second, attention should be paid to the fact that Vincas Kudirka is treated as a figure embodying collective psychic processes by Kavolis in his monographs Sąmoningumo trajektorijos (Trajectories of Consciousness) (1986) and Epochų signatūros (Signatures of Epochs) (1991), summarizing the scientist’s explorations in the field of Lithuanian studies.
Keywords: Vincas Kudirka; Lithuanian national character; collective emotionality; ego identity; Lithuanian studies; social psychology